Understanding Discontinuous Usage Intention of Short Video Platforms: A Social Media Perspective - Zhou Congmin; Siti Hajar Binti Mohamad (Research Parks Publishers, 2025)
The advancement of communication technology and the prevalence of mobile devices have significantly transformed individuals' work and lifestyle patterns. Short video social media has proliferated to fulfil users' demands for social interaction, entertainment, education, and professional engagement. Short video social media has surged in popularity among smartphone users globally. However, over time, when confronted with an abundance of short films that fail to meet expectations, users display negative feelings, such as disappointment, and subsequently lose their intention to utilise the site. Prior research has concentrated on the discontinuous usage intention of social media users; nevertheless, there is a deficiency in comprehensive theoretical investigation and elucidation of the internal mechanisms behind short video users' discontinuous usage intention. This study seeks to investigate the impact of felt overload and perceived value on the discontinuous usage intention of short video consumers. This study develops a discontinuous usage intention model based on the Cognition-Affection-Conation (CAC) theory, Expectancy Disconfirmation theory, and Self-efficacy theory, and proposes the relevant research hypothesis. The perceived overload and perceived value pertain to users' cognition of the platform used for short videos, which affects users' emotions (dissatisfaction). Furthermore, the degree of discontent influences consumers' conation, namely their decision to discontinue usage.